2013
DOI: 10.1002/anie.201302575
|View full text |Cite
|
Sign up to set email alerts
|

Domino Reaction Catalyzed by Zeolites with Brønsted and Lewis Acid Sites for the Production of γ‐Valerolactone from Furfural

Abstract: Take the straight path: Furfural was converted into γ‐valerolactone (GVL) through sequential transfer‐hydrogenation and hydrolysis reactions catalyzed by zeolites with Lewis and Brønsted acid sites (see picture). Together, Zr‐Beta and Al‐MFI nanosheets generated GVL in 78 % yield without the use of precious metals or molecular H2. This system offers an attractive streamlined strategy for the production of GVL from biomass‐derived molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
330
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 394 publications
(344 citation statements)
references
References 48 publications
11
330
1
2
Order By: Relevance
“…Water tolerance is particularly beneficial for cascade reactions, such as the one-pot conversion of furfural to GVL using Zr-Beta and Al-MFI-ns, where certain steps in the process require or produce water. Luo et al (111) showed that GVL yields actually increase from 62% to 68% with the addition of 5 wt% water. The effect of water on reactivity and stability depends on the heteroatom type, the site environment (determined by the zeolite synthesis method), the type of reaction, and the specific solvents and substrates used.…”
Section: Reversible Deactivationmentioning
confidence: 99%
“…Water tolerance is particularly beneficial for cascade reactions, such as the one-pot conversion of furfural to GVL using Zr-Beta and Al-MFI-ns, where certain steps in the process require or produce water. Luo et al (111) showed that GVL yields actually increase from 62% to 68% with the addition of 5 wt% water. The effect of water on reactivity and stability depends on the heteroatom type, the site environment (determined by the zeolite synthesis method), the type of reaction, and the specific solvents and substrates used.…”
Section: Reversible Deactivationmentioning
confidence: 99%
“…Very recently, Roman-Leshkov et al have reported an alternative domino reaction to obtain GVL from furfural in a single reactor. 65 A transfer-hydrogenation reaction, as MPV reaction, has been proposed as an alternative to high-pressure molecular H2 for the selective reduction of carbonyl functional groups. Lewis acid zeolites, particularly Zr-Beta, have been previously introduced as efficient catalysts to perform the MPV reaction for fine chemistry processes.…”
Section: 6-production Of -Valerolactone (Gvl) From Furfuralmentioning
confidence: 99%
“…The overall process proposed by Roman-Leshkov et al requires the combination of zeolites with Lewis and Brönsted acid sites, aproaching a GVL yield of 80% from furfural when Zr-Beta and Al-MFI with nanosheet morphology are used. 65 Figure 11 summarizes the complete reaction mechanism, involving the Lewis acid mediated MPV reduction of furfural into furfuryl alcohol (FA), the Brönsted acid conversion of FA into LA and butyl levulinate, their successive transformation to 4-hydroxypentanoates through a second Lewis acid mediated MPV reaction, and finally GVL formation by lactonization.…”
Section: 6-production Of -Valerolactone (Gvl) From Furfuralmentioning
confidence: 99%
“…It can be converted to the bio-products furfuryl alcohol (FA), furfuryl alkyl ethers (FEs), levulinate esters (LEs), levulinic acid (LA), angelica lactone isomers (AnLs) and -valerolactone (GVL) [2][3][4] (Scheme 1), useful in different sectors of the chemical industry. FA, industrially produced via hydrogenation of Fur, is used in the foundry 3 industry [5], and FEs are used as blending components of gasoline [6,7] and as flavour compounds [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Zeolite beta and its modified versions are known to be effective catalysts for several reactions concerning the valorisation of biomass, e.g. corn fiber to Fur [38]; levuglucosan (an intermediate of (hemi)cellulose pyrolysis) to glucose [39] or Fur [40]; saccharides to Fur [41,42], 5-(hydroxymethyl)furfural (HMF) [42][43][44][45][46][47], or LEs [48,49]; cellulose and hemicelluloses to diesel [50]; hemicelluloses to polyols [51]; C-3 sugar to methyl lactate and lactic acid [52]; FA to 2-(ethoxymethyl)furfural (EMF) and ethyl levulinate (EL) [53]; biodegradable surfactants via acetalisation [54] or etherification of HMF [55]; Fur to GVL [4]; pyrolysis of biomass or derived compounds to aromatic/aliphatic 4 hydrocarbons [56][57][58][59][60][61][62][63][64][65][66]; sugarcane bagasse to bio-oil and upgrading to fuel [67]; co-conversion of biogenic waste and vegetable oil [68]; and pyrolysis of organosolv lignin to phenolic compounds [69,70]. The introduction of different elements into zeolite beta widens its catalytic potential.…”
Section: Introductionmentioning
confidence: 99%